Pertumbuhan dan Produksi Tanaman Bawang Merah Varietas Super Philips Terhadap Pemberian POC Daun Kelor - Harahap, Ariani Syahfitri; Luta, Devi Andriani; Br Sitepu, Sri Mahareni (UNIVERSITAS LABUHANBATU, 2022)
The purpose of this study was to observe the growth and production of the Super Philips variety of shallots against the administration of Moringa leaf POC. The study was conducted in Klambir Lima Village, Hamparan Perak District, Deli Serdang Regency, North Sumatra Province with an altitude of Â± 25 meters above sea level. This research was conducted from January to April 2022. The research method used was a single factor Randomized Block Design (RAK). These factors consisted of 4 treatments, namely: K0 (control), K1 (200 ml/liter water/plot), K2 (400 ml/liter water/plot) and K3 (600 ml/liter water/plot). Parameters observed were plant height, number of tillers, number of leaves, number of tubers per sample, tuber diameter, wet weight of sample per sample, and wet tubers per plot. The data obtained were analyzed using analysis of variance. If the results of the analysis of varieties have a significant difference at = 5%, then proceed with the DMRT test (Duncan Multiple Range Test). The results showed that the best concentration of Moringa leaf POC was 200 ml/liter of water/plot.Â Keywords: shallots, Super Philips, POC, Moring